2006
DOI: 10.1021/jf060669a
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Polyfunctional Thiols in Fresh Lager Beers

Abstract: Polyfunctional thiols are known to have a strong impact on the overall aroma of many fermented foods. Surprisingly, very little data is available on their occurrence in beer. A specific extraction with p-hydroxymercuribenzoic acid was performed on four different fresh light-protected lager beers. gas chromatography-olfactometry, gas chromatography-mass spectrometry, and gas chromatography-pulsed-flame photometer detector analyses of the extracts revealed the presence of more than 10 polyfunctional thiols. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 23 publications
4
95
0
1
Order By: Relevance
“…Sulphur is often produced in stored beer due to Strecker degradation of methionine (Gijs, Chevance, Jerkovic, & Collin, 2002). The excess sulphur is a product of yeast fermentation and is typically found in volatile metabolites (Vermeulen, Lejeune, Tran, & Collin, 2006). The elevated quantities of 5-MTA in aged beer may be due to an interaction between purines and excess sulphur.…”
Section: Discussionmentioning
confidence: 99%
“…Sulphur is often produced in stored beer due to Strecker degradation of methionine (Gijs, Chevance, Jerkovic, & Collin, 2002). The excess sulphur is a product of yeast fermentation and is typically found in volatile metabolites (Vermeulen, Lejeune, Tran, & Collin, 2006). The elevated quantities of 5-MTA in aged beer may be due to an interaction between purines and excess sulphur.…”
Section: Discussionmentioning
confidence: 99%
“…They are found in a wide range of foods (39), including animal products such as yoghurt and cheese, fruits, vegetables, tea, coffee, and alcoholic beverages (2,4,33,35,38). Of particular interest in wine fermentation are the aromatic volatile thiols, 4-mercapto-4-methylpentan-2-one (4MMP), 3-mercaptohexan-1-ol (3MH), and 3-mercaptohexyl acetate.…”
mentioning
confidence: 99%
“…In headspace gas chromatography of cat urine, 3-sulfanyl-3-methylbutan-1-ol and its formate have recently been identified as candidate felinine derivatives. [16] In a previous study dedicated to polyfunctional thiols in lager beers, [7] no sulfanyl formate was found. Only two sulfanyl acetates were found: 2-sulfanylethyl acetate and 3-sulfanylpropyl acetate, both characterized by empyreumatic descriptors.…”
Section: Introductionmentioning
confidence: 94%
“…[4] In beer, 2-sulfanyl-2-methyl-4-methoxybutane has never been detected. [7,8] It is even often used as an internal standard for beer thiol extraction. [9] With the aroma extract dilution analysis technique applied to an aged beer extract, Schieberle revealed the possible relevance of 3-sulfanyl-3-methylbutyl formate to the beer ribes note.…”
Section: Introductionmentioning
confidence: 99%